L’évaluation à distance vécue par les étudiants en situation de handicap - Wathelet, Valérie; Vieillevoye, Sandrine (Médiations et médiatisations, 2022)
In the context of the pandemic, since the June 2020 session, many exams usually scheduled face-to-face have been conducted at a distance. At the institutional level, in April 2020, the support service for students with disabilities and the technical and pedagogical units joined forces to support teachers in organizing their exams and informing students how to prepare and take them. In February 2021, students with disabilities received an online surveyThis survey allowed us to identify difficulties encountered by students, what helps them and what could help them. This allowed us to identify some good practices for teachers and students.
Number: 9